Evaluation of tubal patency by hysterosalpingo-contrast Sonography (HyCoSy): Controversies, dilemmas and considerations - Zining Xu; Yaoting Wang; Juan Sun; Shuangxi Chen; Zou Yan; Chen Lin; Jing Shu (Heliyon, 2023)
Evaluation of tubal patency is one of the vital steps in the process of female infertility management. Hysterosalpingo-contrast Sonography (HyCoSy) has become the first-line recommendation for evaluating tubal patency. However, there remain some controversies and dilemmas relevant to the evaluation of tubal patency by HyCosy, with no effective solution has been proposed or no consensus has been reached. Herein, combined with previous research and clinical experience, we conclude and analyze these controversies and dilemmas, aiming at offering our perspective on the opportunities and challenges which are faced by HyCosy.